Ampharetidae (Annelida: Polychaeta) from Japan. Part I: The genus Ampharete Malmgren, 1866, along with a discussion of several taxonomic characters of the family and the introduction of a new identification tool - Imajima, Minoru; Reuscher, Michael G.; Fiege, Dieter (Zootaxa, 2012)
Five species of Ampharete are reported from Japan. Two species, Ampharete ampullata sp. nov., and Ampharetecinnamomea sp. nov., are newly described, and Ampharete falcata, is newly recorded from the North Pacific. Severalmorphological characters are reviewed and their value for taxonomy and systematics is discussed. A schematic diagram of the anterior end of ampharetid polychaetes, which may serve as the species’ “ID card”, is introduced.